2018
DOI: 10.1021/acs.inorgchem.8b01526
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Phonon Driven Negative Thermal Expansion in Cubic GaFe(CN)6 Prussian Blue Analogues

Abstract: The understanding of the negative thermal expansion (NTE) mechanism is vital not only for the development of new NTE compounds but also for effectively controlling thermal expansion. Here, we report an interesting isotropic NTE property in cubic GaFe(CN) Prussian blue analogues (α = -3.95 × 10 K, 100-475 K), which is a new example to understand the complex NTE mechanism. A combined study of synchrotron X-ray diffraction, X-ray total scattering, X-ray absorption fine structure, neutron powder diffraction, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 60 publications
(88 reference statements)
4
34
0
Order By: Relevance
“…The sample was held at 475 K for 1 h to ensure an anhydrous state, and then the SXRD data of TiCo­(CN) 6 were collected during the cooling process. TiCo­(CN) 6 displays a linear NTE relationship from 475 to 100 K with a linear CTE (α l ) of −4.05 × 10 –6 K –1 (Figure ), which is similar to that of GaFe­(CN) 6 (α l = −3.95 × 10 –6 K –1 , 100–475 K) but smaller than those of ScCo­(CN) 6 (α l = −6.6 × 10 –6 K –1 , 25–600 K) and CdPt­(CN) 6 (α l = −6.65 × 10 –6 K –1 , 375–25 K) . Gao et al proposed the concept of average atomic volume (AAV), i.e., the average volume of atoms occupying a unit cell [AAV = V / ZN , where V = unit cell volume, Z = cell formula units, and N = number of atoms in the chemical formula], aiming to evaluate, explore, and design NTE compounds with open-framework structure.…”
mentioning
confidence: 76%
“…The sample was held at 475 K for 1 h to ensure an anhydrous state, and then the SXRD data of TiCo­(CN) 6 were collected during the cooling process. TiCo­(CN) 6 displays a linear NTE relationship from 475 to 100 K with a linear CTE (α l ) of −4.05 × 10 –6 K –1 (Figure ), which is similar to that of GaFe­(CN) 6 (α l = −3.95 × 10 –6 K –1 , 100–475 K) but smaller than those of ScCo­(CN) 6 (α l = −6.6 × 10 –6 K –1 , 25–600 K) and CdPt­(CN) 6 (α l = −6.65 × 10 –6 K –1 , 375–25 K) . Gao et al proposed the concept of average atomic volume (AAV), i.e., the average volume of atoms occupying a unit cell [AAV = V / ZN , where V = unit cell volume, Z = cell formula units, and N = number of atoms in the chemical formula], aiming to evaluate, explore, and design NTE compounds with open-framework structure.…”
mentioning
confidence: 76%
“…As shown in Figure 2b, it is interesting to observe that the present AgB(CN) 4 exhibits a large isotropic NTE behavior in a wide temperature range (α v = −40 × 10 −6 K −1 , 100−600 K). The NTE behavior of AgB(CN) 4 is stronger than the most popular NTE materials ZrW 2 O 8 7 and ScF 3 8 and stronger than most PBAs, such as GaFe(CN) 6 , 22 but smaller than (Zn,Cd)(CN) 2 . 11 Furthermore, the present AgB(CN) 4 shows a wide NTE range, which can be comparable to those in the electronic-driven functional 13 and M(CN) 2 (M = Zn or Cd).…”
mentioning
confidence: 90%
“…It was found that NTE is induced by the transverse vibrations of the atomic -M-N≡C-M'-linkages through a tension mechanism, since both M-N and M'-C bonds are much softer to bend than to stretch. However, the main vibrational contribution to the NTE comes from the N atoms, since the relative transverse vibrations of the M-N bonds are much larger than that of the M'-C bonds [Figure 17] [113][114][115] . shows the resulting anisotropy of the relative thermal vibrations.…”
Section: Negative Thermal Expansion Materialsmentioning
confidence: 99%
“…However, it can be observed that the main contribution comes from the Ga-N thermal vibrations. Figure taken from Ref [113]. .…”
mentioning
confidence: 99%